Character Education In Islamic Perspective - Sri Mulyani (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2018)
Character education in Indonesia is a necessity. The increasing crime rate and the various cases of moral deviation signify that the character of majority citizens is at alarming state. Constitutionally, the aim of national education is not only generating skilled and intelligent human, but also noble-characterized human. This is stipulated in the policy guidelines of character education which include 18 characters excel (religious, honest, disciplined, tolerant, and so on). In Islamic perspective the term character education is similar to Akhlak (Islamic ethics) education. The primary sources of character education in Islam are the Qur’an and Hadith; and the Prophet Muhammad SAW as the role model. The recommended method in the application of character education in Islam based on mental-spiritual approach through soul management, habituation, exemplary, and healthy environment which involve three education centers, namely schools, families, and communities.